Robust adaptive sliding mode control of a bidirectional DC-DC converter feeding a resistive and CPL based on PSO - Cham, Julius Derghe; Koffi, Francis Lénine Djanna; Boum, Alexandre Teplaira; Harrison, Ambe (Institute of Advanced Engineering and Science, 2024)
A DC-DC converter functioning in bidirectional (two-way) mode is a crucial component of direct current (DC) microgrids since it allows electricity to flow in both directions. However, because of load changes and other factors, the DC-bus voltage might become unstable. This research proposes a robust adaptive controller for a half-bridge two-way DC-DC converter founded on particle swarm optimization (PSO). Using a DC-DC half-bridge bidirectional converter, the effectiveness of various conventional and proposed control techniques is investigated. In comparison to a conventional sliding mode controller (CSMC), it is found that a PSO-based sliding mode control with an adaptive law is the optimal control approach for a bidirectional half-bridge DC-DC converter. This is because minimal steady-state error and the shortest rising and settling times are guaranteed. The benefits of robustness, chattering reduction, and simple design are combined in the suggested controller, which is especially beneficial when dealing with load and input voltage changes. The controller ensures robustness and stability in the face of parameter changes. Numerical simulations conducted in a MATLAB-Simulink environment on a DC-DC half-bridge converter operating in bidirectional mode show the controller's improved performance over its existing counterpart.